2013
DOI: 10.1074/jbc.m113.466193
|View full text |Cite
|
Sign up to set email alerts
|

The N and C Termini of ZO-1 Are Surrounded by Distinct Proteins and Functional Protein Networks

Abstract: Background: Biotin ligase tagging with ZO-1 was applied to identify a more complete tight junction proteome. Results: Identical but also different proteins and functional networks were identified near the N and C ends of ZO-1. Conclusion:The ends of ZO-1 are embedded in different functional subcompartments of the tight junction. Significance: Biotin tagging with ZO-1 expands the tight junction proteome and defines subcompartments of the junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
118
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 95 publications
(60 reference statements)
7
118
1
Order By: Relevance
“…Similar to what we had found using this method with ZO-1 (Van Itallie et al, 2013), our results suggest that E-cadherinbiotin-ligase (EcadBL) identifies a large number of known functionally relevant proteins as well as proteins previously not known to be near E-cadherin and which might provide novel insights about E-cadherin function. The most abundant proteins identified were catenins, including a-E-catenin, b-catenin, p120 catenin and plakoglobin, and unexpectedly, a-N-catenin and a-Tcatenin.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Similar to what we had found using this method with ZO-1 (Van Itallie et al, 2013), our results suggest that E-cadherinbiotin-ligase (EcadBL) identifies a large number of known functionally relevant proteins as well as proteins previously not known to be near E-cadherin and which might provide novel insights about E-cadherin function. The most abundant proteins identified were catenins, including a-E-catenin, b-catenin, p120 catenin and plakoglobin, and unexpectedly, a-N-catenin and a-Tcatenin.…”
Section: Introductionsupporting
confidence: 72%
“…2A); a prominent band at ,135 kDa was detected with an anti-E-cadherin antibody and is likely the EcadBL fusion protein. Unlike the results obtained with ZO-1 biotin ligase fusions (Van Itallie et al, 2013), the E-cadherin fusion protein was not the most abundant biotinylated protein in these cells, possibly because the E-cadherin intracellular domain available for self-biotinylation contains only five lysines. Three similar Coomassie-stained protein gel lanes from independent labeling experiments and streptavidin purifications were each cut into 12 bands (top to bottom) and used for proteomic analysis by mass spectrometry.…”
Section: Ecadbl Fusion Protein Localizes To Cell-cell Contacts In MDCcontrasting
confidence: 46%
See 1 more Smart Citation
“…Previous application of BioID to lamin A (LaA) suggested that a majority of the candidates resided within ∼20-30 nm of nuclear envelope (NE)-associated LaA (1). Significantly, distinct subsets of BioID candidates were identified when BirA* was fused to the N versus the C terminus of the cell-junction protein ZO-1 (3). These studies suggested that BioD has a limited nanometer-scale (<20 nm) labeling radius.…”
mentioning
confidence: 87%
“…Issues related to bait (and prey) protein solubility and the stability and/or duration of their interaction are thus overcome. BioID has been used successfully to screen for constituents of the relatively insoluble mammalian nuclear lamina (1), the trypanosome bilobe (2), cell junction complexes (3)(4)(5), and centrosomes (6,7). The method also has been used to screen for proteins involved in the Hippo signaling pathway (8).…”
mentioning
confidence: 99%